Leachate Using Cambination Of Chemical And Physical Method - Mohd Tadza, Mohd Yuhyi (Universiti Sains Malaysia, 2005)
Ammonia is a common contaminant found in landfill leachate. Ammonia is toxic even in small quantity and can affect water life forms and also hazardous to human being. Leachate is a liquid formed when water due to precipitation passes through the waste in landfill and transport pollutant and continue to migrate to the base of the landfill cell and often percolate into the ground thus contaminate groundwater reservoir and the environment. In order to protect and preserve the environment, leachate must be thoroughly treated before discharging it to the environment. A study was conducted on removal of leachate quality parameters such as ammonia, total COD and phosphorus concentration at Pulau Burung Level III Sanitary Landfill by physico-chemical series of treatment starting from Magnesium Ammonium Phosphate (MAP) precipitation, followed by aeration process and finally adsorption using natural zeolite through batch and column test. Approximately 85-90% of ammonia was removed during the pretreatment of MAP alone, and the COD concentrations were reduced up to 60% during the aeration and zeolite adsorption. Phosphorus contents were no longer a threat as all the samples were reduced to 0 mg/L for all sample. Other than obtaining a final effluent of standard B, the treatment byproduct produced by the precipitation can be beneficial as the sludge have the same properties that of commercial fertilizer used for agricultural purposes.